National assessment on the frequency of pain medication prescribed for intrauterine device insertion procedures within the Veterans Affairs Health Care System - Anna D. Ware; Terri L. Blumke; Peter J. Hoover; Zach P. Veigulis; Jacqueline M. Ferguson; Malvika Pillai; Thomas F. Osborne (PLoS ONE, 2025)
Background The intrauterine device (IUD) is a highly effective form of long-acting reversible contraception, widely recognized for its convenience and efficacy. Despite its benefits, many patients report moderate to severe pain during and after their IUD insertion procedure. Furthermore, reports suggest significant variability in pain control medications, including no adequate pain medication. The aim of this evaluation was to assess the pharmaceutical pain medication types, proportions, and trends related to IUD insertion procedures within the Veterans Health Administration (VHA). Methods IUD insertion procedures documented in the VA electronic health record were assessed from 1/1/2018 to 10/13/2023. Descriptive statistics described patient and facility characteristics while annual trends were assessed using linear regression. Results Out of the 28,717 procedures captured, only 11.4% had any form of prescribed pain medication identified. Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) were the most frequently prescribed pain medication category (8.3%), with ibuprofen being the most common pain medication overall (6.1%). Over the assessment period, there was an average annual increase of 0.52% ( p = 0.038) of procedures with prescribed pain medication, increasing from 10.3% in 2018 to 13.3% in 2023. Conclusions Although IUD insertion procedures have been seeing an increase in prescribed pain medication, the overall proportion remains disproportionality low relative to the pain experienced. Additionally, when pain interventions were initiated, they disproportionally utilized medication that have been shown to be ineffective. The intent of the work is that the information will help guide data driven pain medication strategies for patients undergoing IUD insertion procedures within the VHA.